2021
DOI: 10.1021/acsbiomaterials.0c01644
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Indocyanine Green-Based Codelivery Nanoplatforms for Combinatorial Therapy

Abstract: Indocyanine green (ICG), a near-infrared (NIR) agent with an excellent imaging performance, has captivated enormous interest from researchers owing to its excellent therapeutic and imaging abilities. Although various nanoplatforms-based drug delivery systems (DDS) with the ability to overcome the clinical limitations of ICG has been reported, ICG-medicated conventional cancer diagnosis and photorelated therapies still lack in exhibiting the therapeutic efficacy, resulting in incomplete or partly tumor eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 185 publications
(288 reference statements)
1
22
0
Order By: Relevance
“…We have chosen ICG since it is an FDA-approved chromophore with a long-standing history in clinical applications and clinical research related to optical imaging and laser-based therapeutics. 16,17 ICG has also been encapsulated into RBC-based delivery systems for optical imaging and light-based theranostics. 18,19 We present results that demonstrate that the surface area, volume, and deformability of RBC ghosts ICG are significantly reduced as compared to RBCs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have chosen ICG since it is an FDA-approved chromophore with a long-standing history in clinical applications and clinical research related to optical imaging and laser-based therapeutics. 16,17 ICG has also been encapsulated into RBC-based delivery systems for optical imaging and light-based theranostics. 18,19 We present results that demonstrate that the surface area, volume, and deformability of RBC ghosts ICG are significantly reduced as compared to RBCs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We refer to these materials as RBC ghosts ICG since in a similar fashion to the common methodologies used in the fabrication of RBC-based delivery systems containing other cargos, the construction process is based on the formation of hemoglobin-depleted RBC ghosts as an intermediate structure, which, in this case, becomes loaded with ICG. We have chosen ICG since it is an FDA-approved chromophore with a long-standing history in clinical applications and clinical research related to optical imaging and laser-based therapeutics. , ICG has also been encapsulated into RBC-based delivery systems for optical imaging and light-based theranostics. , …”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Organic small-molecule photosensitizers have shown great potential in tumor phototherapy owing to their excellent biocompatibility, low toxicity, facile molecular tailoring and adjustable absorption wavelength. 38,41 Various kinds of organic small-molecule photosensitizers, including cyanine dyes, [42][43][44][45] porphyrins, [46][47][48][49] BODIPY derivatives [50][51][52][53] and conjugated small molecules that contain donor-acceptor (D-A) structures, 38,54 have been developed for PTT and PDT. Among them, organic conjugated small molecules with D-A, D-A-D or A-D-A structures have gradually gained favor.…”
Section: Bing Lumentioning
confidence: 99%
“…8−13 Previous studies had shown that the Food and Drug Administration (FDA)approved, near-infrared (NIR)-active, indocyanine green (ICG), along with doxorubicin (DOX), is exceedingly effective against a wide range of cancers. 14 ICG-induced PTT is effective only against primary cancer cells and not against metastatic cells. 1,15 However, chemotherapy using DOX is inadequate to cure the primary tumor and is commonly practiced during postsurgery treatment.…”
Section: Introductionmentioning
confidence: 97%
“…2,6,14 In recent advancements, several ICG-DOX nano-codelivery systems such as inorganic nanoparticles, polymeric nanoparticles, liposomes, and protein-based nanoparticles have been studied for chemo-PTT. 14 The polymer-based PLGA-lecithin-PEG nanoparticle showed an efficient chemo-PTT effect (ICG and DOX), prompting better apoptosis/killing of DOX-resistant Michigan Cancer Foundation-7 (MCF-7)/adriamycin (ADR) cells. 16 Here, the in vivo reduction in tumor size with no recurrence was also observed.…”
Section: Introductionmentioning
confidence: 99%